Integrated application of multi-omics and biochemical analysis revealed the physiological response mechanism of ammonia nitrogen tolerance in the razor clam (Sinonovacula constricta) - Sun, Gaigai; Lv, Liyuan; Yao, Hanhan; Lin, Zhihua; Xu, Nianjun; Dong, Yinghui (Frontiers in Marine Science, 2024)
As one of the major limiting environment factors in aquaculture, ammonia nitrogen brings severe threat to the growth and survival of aquatic animals, especially mollusk in benthic zones. However, the molecular mechanism underlying the toxic response and tolerance of mollusks to ammonia nitrogen remain unclear. In this study, transcriptome, metabolome and physiological indicators were combined to investigate the metabolic mechanism of adult razor clam (Sinonvacula constricta), which was exposed to 46mg/L ammonia nitrogen for 1 day (A1) and 10 days (A10). It was observed that compared with A1, the contents of free amino acids, including taurine (Tau), alanine (Ala) and arginine (Arg), the activities of immune-related enzymes acid phosphatase (ACP) and alkaline phosphatase (AKP), and antioxidation-related enzymes superoxide dismutase (SOD) and glutathione peroxidase (GPX) in hepatopancreas, were significantly increased in A10, while the content of malondialdehyde (MDA) was significantly decreased (P < 0.05). Furthermore, the contents of glucose and pyruvate in hepatopancreas, foot and hemolymph urea nitrogen (HUN) were significantly changed (P < 0.05). Meantime, the comparative transcriptome analysis between A1 and A10 groups revealed the effects of ammonia stress on immune defense, antioxidant system and metabolic pathway. Likewise, metabolomic analysis showed that ammonia exposure interfered with amino acid metabolism, lipid metabolism and carbohydrate metabolism, with metabolism related-genes changed according to RNA-seq analysis. By comparing the metabolites and transcripts profiles of A10 and A1, the expression of some genes involved in detoxification and ammonia excretion was significantly changed. Combined with the changes in metabolites, we speculated that the convert endogenous ammonia to alanine, alanine-glucose cycle and urea synthesis might be adaptive strategies of the razor clam after ammonia stress. Collectively, the combination of physiological, transcriptome and metabolome will greatly contribute to the progressively understand the toxicity of ammonia exposure and the defense mechanism of razor clam against ammonia toxicity, and provide new sights on the potential molecular mechanisms of ammonia adaptive strategies in benthic mollusk.